Hallucinations, Dreaming, and Frequent Dozing in Parkinson Disease: Impact of Right-hemisphere Neural Networks - Karina Stavitsky; Patrick McNamara; Raymon Durso; Erica Harris; Sanford Auerbach; Alice Cronin‐Golomb (2008)
Objective To relate sleep disturbances in Parkinson disease (PD) to hemispheric asymmetry of initial presentation. Background Sleep disturbances are common in PD arising from the neurodegenerative process underlying the disease, which is usually lateralized at onset. Patients with left-side Parkinson disease onset (LPD: right hemisphere dysfunction) exhibit reduced vigilance relative to those with right-side Parkinson disease onset (RPD: left hemisphere dysfunction), leading us to hypothesize that sleep-related disturbances, particularly excessive daytime sleepiness, would be more severe for LPD than for RPD. Methods Thirty-one nondemented participants with PD (17 RPD and 14 LPD) and 17 age-matched control (CO) participants with chronic health conditions were administered the Parkinson Disease Sleep Scale and polysomnography was performed on a subset of the PD participants. Results Both PD subgroups exhibited more nighttime motor symptoms than the CO group, but only LPD endorsed more nocturnal hallucinations and daytime dozing. Controlling for mood additionally revealed more vivid dreaming in LPD than RPD. There were no significant differences between LPD and RPD on measures of sleep architecture. Conclusions Increased dreaming, hallucinations, and daytime somnolescence in LPD may be related to changes in right-hemisphere neural networks implicated in the generation and control of visual images, arousal, and vigilance. Our results underscore the need to consider side of onset in regard to sleep disturbances in PD.